Single-dose ceftriaxone versus multiple-dose trimethoprim-sulfamethoxazole in the treatment of acute urinary tract infections. - Iravani, A (1985)
Fifty-four college women with symptoms of lower urinary tract infections were randomly treated, 25 with 500 mg of ceftriaxone in a single intramuscular dose and 29 with 160 mg of trimethoprim-800 mg of sulfamethoxazole orally twice daily for 7 days. At 1 week after treatment, 23 patients (92%) in the ceftriaxone group and 28 patients (96%) in the trimethoprim-sulfamethoxazole group were cured. Responses of the patients with positive or negative antibody-coated bacteria tests were not significantly different. Four patients (16%) in the ceftriaxone group developed diarrhea and malaise. One patient (4%) in the trimethoprim-sulfamethoxazole group had medication discontinued because of headaches. Leukopenia was found in one patient (4%) in the ceftriaxone group and four patients (14%) in the trimethoprim-sulfamethoxazole group.